Status Gizi dengan Kelelahan Kerja Karyawan Bagian Proses dan Teknik Pabrik Kelapa Sawit - Rofiq Alfikri; Rd. Halim; Muhammad Syukri; Lia Nurdini; Fahrul Islam (STIKes Hang Tuah Pekanbaru, 2021)
Fatigue is a contributor to half of work accidents. In addition, severe fatigue is the number 2 killer after heart disease. The purpose of this study was to determine the relationship between nutritional status, duration of work, and noise level with work fatigue on employees of the process and engineering division of the PT.X Palm Oil Mill. This study was a quantitative study with a cross-sectional approach with a total of 33 respondents. Sampling was taken using total sampling technique. Data analysis was performed univariate and bivariate using chi-square test. The results showed that most respondents had a Body Mass Index (BMI) of 18.5-25 at 48.5%. Most respondents have a work duration of 12 hours by 48.5%. The maximum noise level is 85dB by 39.4%. Most work fatigue is in the low category of 39.4%. The results of statistical tests showed that there was a relationship between nutritional status and fatigue (p value = 0.007 PR=8.5 95%CI 1.2-59.5), there is no relationship between work duration and fatigue (p value = 1,000 PR=0,8 95%CI 0,2-3,1), and there is no relationship between noise level and fatigue (p value = 0.701 PR=1,5 95%CI 0,5-4,8). The conclusion of this study is that nutritional status is associated with work fatigue. It is hoped that the company will make a healthy canteen in an effort to improve the nutritional status of workers.